Halide Perovskite Nanocrystal Emitters. Issue 3 (28th January 2021) - Liu, Maning; Grandhi, G. Krishnamurthy; Matta, Sri; Mokurala, Krishnaiah; Litvin, Aleksandr; Russo, Salvy; Vivo, Paola
Abstract : The increasing attention on halide perovskite nanocrystals (PNCs) stems from their outstanding optoelectronic properties, especially the intriguing photoluminescence (PL) features. The high photoluminescence quantum yields (up to unity) of PNCs, and the tunability of their optical bandgaps by composition engineering and quantum confinement effects, account for the demonstrated great potential in several optoelectronic applications, such as light‐emitting diodes (LEDs), phosphors, lasers, and photodetectors. However, despite the rapid growth of this research field, several questions are still left unanswered and there is room for further improving the luminescence performance, particularly for emerging lead‐free PNC compositions. Herein, the recent advances in the light emission phenomena in PNCs are discussed. A special focus is given to the correlation between PL and phase transition, the dual‐color emission, the tunability of the PL toward near‐infrared (NIR), and the thermal quenching effect. The key research findings on LEDs, the major application of perovskite‐based nanoscale emitters, are also outlined. Finally, the view on the most urgent challenges to be addressed is provided, with the intent of promoting a more profound understanding of PNC emission‐related phenomena in the future. Abstract : Low‐dimensional (0D–2D) metal halide perovskite nanocrystals (PNCs), with facile PL tunability, are the rising star in luminescent materials. The next generation of PNCs ‐based optoelectronics with high performance and stability is foreseen through manifold engineering methods (e.g., on composition and surface) and with the support of advanced theoretical modeling.